Force titration of amino group-terminated self-assembled monolayers of 4-aminothiophenol on gold using chemical force microscopy - Mu, Tao (2012)
Chemical force microscopy (CFM) was used to measure the adhesion force between NH2-terminated probe tip and gold substrate modified with self-assembled monolayers (SAMs) of 4-aminothiophenol (4-ATP). The curve of adhesion force as a function of solution pH value (force titration curve) was obtained. The pK1/2 of surface NH2 group of 4-ATP SAMs obtained from the force titration curve is 5.3, comparable with pK1/2=4.9 determined by the conventional contact angle titration.